2021
DOI: 10.3126/ajms.v12i6.36687
|View full text |Cite
|
Sign up to set email alerts
|

Study of depression, anxiety and stress among first year Medical students in Government Medical College, Himachal Pradesh during COVID-19 pandemic

Abstract: Background: During COVID 19 pandemic many countries implied nationwide lockdown which affected academic and educational activities of medical students. We evaluated the level of depression, anxiety and stress among first MBBS students of Government Medical College, Himachal Pradesh. Aims and Objective: To estimate the level of depression, anxiety and stress among first MBBS students during COVID-19 pandemic and study its relationship with gender. Materials and Methods: A standard questionnaire DASS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Whereas, Rana et al study had higher proportion of female medical students suffering from moderate depression (38%) and moderate anxiety (44%) but mild stress (67%). 12 In our study, a higher proportion of male medical students had moderate depression (12.88%), moderate anxiety (17.42%), and mild stress (13.64%) during COVID-19 duty. In the study by Rana et al male medical students showed moderate depression (39%) but had severe anxiety (31%), and moderate stress (16%).…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Whereas, Rana et al study had higher proportion of female medical students suffering from moderate depression (38%) and moderate anxiety (44%) but mild stress (67%). 12 In our study, a higher proportion of male medical students had moderate depression (12.88%), moderate anxiety (17.42%), and mild stress (13.64%) during COVID-19 duty. In the study by Rana et al male medical students showed moderate depression (39%) but had severe anxiety (31%), and moderate stress (16%).…”
Section: Discussionmentioning
confidence: 43%
“…11 Whereas, in a Himachal Pradesh study conducted by Rana et al 48%, 74%, and 32% of medical students were found to be suffering from depression, anxiety, and stress, respectively as a result of the COVID-19 outbreak, which is higher as compared to our study. 12 Natalia et al study identified a higher prevalence of stress (44.6%) compared to depression (18.6%). While in our study depression was found to be more than stress.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The study results indicated that, among the subjects those who were staying at personal home have suffered more from depression and stress than those who are staying at dormitory. 14 Based on the results of this study, we suggest that colleges and universities should provide students with tailored psychological guidance, considering that college students in different years may have differentiated psychological wellbeing status. Universities may offer proper psychological counseling for freshman students in order to relieve their anxiety and pay special attention to improving the psychological well-being of sophomore students.…”
Section: Discussionmentioning
confidence: 79%
“…Item 1,6,8,11,12,14 and 18 belonged to stress scale, item 3,5,10,13,16,17, and 21 to the depression scale and item 2,4,7,9,15,19 and 20 to the anxiety scale.Each question was scored from 0 to 3. If a student scored >14 for depression,>10 for anxiety and > 19 for stress, they were referred for further counseling.27 …”
mentioning
confidence: 99%